Enhancement of the in-field critical current density of trifluoroacetate metal organic deposition derived (Y0.77Gd0.23)Ba2Cu3Oy films by annealing of CeO2 buffered R-Al2O3 substrates. (25th April 2019) - Sakuma, Keita; Sato, Michio; Miura, Masashi
Abstract: We investigate the superconducting properties of (Y0.77 Gd0.23 )Ba2 Cu3 O y [(Y, Gd)BCO] films on as-grown and annealed (600 °C–1000 °C) CeO2 buffered R -plane sapphire ( R -Al2 O3 ) substrates using trifluoroacetate metal organic deposition (TFA-MOD). The annealing was found to improve the crystallinities of not only the CeO2 buffer layers but also the (Y, Gd)BCO films. Although the anneal had no apparent effect on the pinning centers of the (Y, Gd)BCO films, the in-field J c of the (Y, Gd)BCO films grown on the CeO2 buffered substrates improved with increasing annealing temperature. The present results are discussed in terms of the crystallinities and J c values of the (Y, Gd)BCO films.